Faktor-faktor yang Mempengaruhi Kinerja Pegawai: Studi di Perusahaan Daerah Pasar Tohaga Kabupaten Bogor - Ma'arif, M.Syamsul; Sukmawati, Anggraini; Damayanthy, Dessy (Universitas Brawijaya, Indonesia, 2013)
Employees are the most valuable asset in every organization. The purpose of this study is toanalyze and determine the dominant factors that affect employee performance. Latent variables in this study are individual factors, psychological factors, and organizational factors as exogenous variables as well as performance of the employee as the endogenous variable. The results obtained from Partial Least Square (PLS) analysis suggest that employee performance is determined by creativity and innovation. Employeeperformance is influenced by individual factors and psychological factors. Individual factors that influence employee performance are reflected by indicators of ability and skill. Psychological factors that directly affect performance of the employees are represented by the learning process. While organizational factors reflected by leadership, job design, and, supervision do not affect employees performance.